Manajemen Program Literasi Sekolah dalam Meningkatkan Kemampuan Membaca Siswa - Moch Muschlih R; Reza Refhana Faisal; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
This study aims to describe the implementation of school literacy programs in improving students' reading skills. The approach used in this study is a case study. Data collection methods use interviews, observations, and document studies. The selection of respondents or samples is done by purposive sampling. The selected samples are used as primary data. The research findings show that (1) Planning has been structured, including setting targets, arranging activity schedules, and providing literacy support facilities; (2) Organization, there is a division of tasks between the principal, educators, and other school components; (3) Implementation, the literacy program is carried out through 15-minute reading activities, integrating literacy into the learning process, and providing special guidance for students who still have difficulty reading; (4) Supervision is carried out through routine evaluations and reflection activities on the progress of the program. The conclusion of this study is that school literacy program management can improve students' reading skills if it is carried out continuously and in a structured manner.